EVALUATION OF FORMATIVE USABILITY ON WEBSITE PROTOTYPE OF PENGELOLAAN TENAGA KERJA PENUNJANG TELKOM DIRECTORATE OF DIGITAL BUSINESS - Almaidah, Ditasari
In 2021 Telkom Directorate of Digital Business (Telkom DDB) developed a website for the manage one of their worker groups, namely Tenaga Kerja Penunjang (TKP). TKP is a term for contract workers at PT. Telkom. Currently, the website is still in prototype format and has not been yet launched to the market. Before the website launch, it is necessary to evaluate the usability of the product to target users for ensure the website can be used easily. This study was conducted to determine the usability of website pengelolaan TKP. The methods used for data collection were formative evaluation. There are five test task to evaluate the website. The usability parameters used are task success rate to measure effectiveness, lostness score to measure efficiency, and system usability scale to measure satisfaction. This usability evaluation also equipped with retrospective think aloud (RTA). During the process of working on the task test, participants also wearing an electroencephalogram (EEG) to measure the mental workload that participant received. Mental workload is measured by beta/alpha wave ratio. Beta/alpha wave ratio >= 1 indicates menta workload received is high. The study was conducted on 12 participants who were asked to do five lists of test tasks. The results showed that website pengelolaan TKP was not yet fully effective and efficient because task four had a percentage of successful completion of task 67% (task success rate > 70% = effective) and task three had a lostness score of 0.479 (lostness score < 0.4 = efficient). The mental workload received by participants when doing tasks three and four was high ( beta/alpha wave ratio = 1.153 and 1.092). The average result of the SUS questionnaire is 65.83 out of 100, this value indicates the website is in the marginal category so it needs to be improved. Through the RTA, 12 proposed priority improvement designs for website pengelolaan TKP.